Reconsidering the Tariff reform controversy in Britain: Joseph Chamberlain's tariff reform versus Arthur Balfour's plan of retaliatory tariffs - Tomoari Matsunaga (The Journal of European Economic History (JEEH), 2021)
The studies on the tariff reform movement from 1903 to 1913 inBritain can be classified into three main approaches, emphasising re-spectively: 1) a protectionist strategy to revive British industry, 2) anelectoral strategy to widen the base of the Unionists or the Conser-vative Party, and 3) an imperial strategy to unite the British Empirethrough imperial preference. On the basis of new evidence, this studyrefutes the first and second views, and supports the third. However,even those scholars upholding the third view have not maintainedthat the domestic and imperial sides of tariff reform were unrelated.This study demonstrates instead that they were actually disconnectedand that in order to achieve the unity of the British Empire, JosephChamberlain and leading tariff reformers formed a plan prioritizingthe interests of the self-governing colonies or dominions over Britain'sown national interests. In their vision, even if their scheme of tariff re-form were to strengthen the dominions' economies rather than thehome economy, it should be accepted as long as it reinforced theunity of the British Empire. To elucidate this point, we analyse UnionistPrime Minister Arthur Balfour's retaliatory tariff plan in comparisonwith Chamberlain's tariff reform. A new perspective that refutes thegenerally accepted view of Balfour's plan as a compromise betweentariff reform and free trade will also be suggested.
Keywords: 330